2020
DOI: 10.1017/s0022215120002121
|View full text |Cite
|
Sign up to set email alerts
|

A rise in facial nerve palsies during the coronavirus disease 2019 pandemic

Abstract: Objective An increase in spontaneous lower motor neuron facial nerve (VIIth cranial nerve) palsies was seen during the severe acute respiratory syndrome coronavirus 2 outbreak in our emergency clinic. This led us to perform a single-centre cohort review. Methods A retrospective review was conducted of VIIth cranial nerve palsies from January to June 2020 and the findings were compared to those cases reviewed in the previous year. The severe acute respiratory syndrome coronavirus 2 incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 17 publications
2
36
0
1
Order By: Relevance
“…Studies have been published regarding the increased peripheric acute facial paralysis during COVID-19 pandemic. Direct viral neurophism or immune-mediated mechanism secondary to increased pro-inflammatory cytokines may cause facial paralysis in COVID-19 [ [11] , [12] , [13] , [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been published regarding the increased peripheric acute facial paralysis during COVID-19 pandemic. Direct viral neurophism or immune-mediated mechanism secondary to increased pro-inflammatory cytokines may cause facial paralysis in COVID-19 [ [11] , [12] , [13] , [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the SARS-CoV-2 pandemic has infected over 45 million worldwide. It possible that this patient's presentation was a coincidence, this patient presented as the incidence of SARS-CoV-2 was declining 17 in the region, and the incidence of FNP has increased during the SARS-CoV-2 pandemic, 18 which suggests a relationship between his BP and SARS-CoV-2 diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, Zammit et al conducted a retrospective review of VIIth cranial nerve palsies in the first half of 2020 compared to cases in 2019. 4 The authors found that the VIIth cranial nerve palsy incidence in the 2020 period was 3.5 per cent and significantly higher than last year's rate of 1.3 per cent ( p < 0.01). The authors hypothesise that severe acute respiratory syndrome coronavirus 2 may be responsible for an increased number of facial nerve palsies and advise clinicians to be aware of this as an initial presentation of the disease.…”
mentioning
confidence: 90%